2005
DOI: 10.1080/14647270500030266
|View full text |Cite
|
Sign up to set email alerts
|

Dietary oestrogens and male fertility potential

Abstract: Reports of increased incidences of male reproductive abnormalities and falling sperm counts have prompted interest into the nature of these threats to global fertility. Xenoestrogens have been flagged as major culprits but to date, little is known about the effects of dietary phytoestrogens on male reproductive health. These non-steroidal oestrogens of plant origin are potent endocrine disruptors that modulate normal physiological functions. Phytoestrogens have become a major component in the typical Western f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…[42] Intake of excess isoflavanoids (phytosterol) during child hood may lead to moderate decrease in male fertility, including reproductive capacity. [43] In an earlier report, we presented evidence on the effect of GA 3 on serum enzyme and biomarkers and on lipids, and blood cell count in male rat. [19] In this study, we demonstrate that GA 3 as a terpenoid plant hormone is capable of modulating rat testicular function.…”
Section: Discussionmentioning
confidence: 99%
“…[42] Intake of excess isoflavanoids (phytosterol) during child hood may lead to moderate decrease in male fertility, including reproductive capacity. [43] In an earlier report, we presented evidence on the effect of GA 3 on serum enzyme and biomarkers and on lipids, and blood cell count in male rat. [19] In this study, we demonstrate that GA 3 as a terpenoid plant hormone is capable of modulating rat testicular function.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, exposure to isoflavone during gestation and lactation (dietary exposure) or perinatally (oral gavage) yielded, once again, inconsistent results. While some reports found no reproductive defects (Fielden et al, 2003;Kang et al, 2002;Nagao et al, 2001), others reported variable persistent phenotypic and behavioral reproductive abnormalities such as decreased testicular weight or size (Atanassova et al, 2000;West et al, 2005;Wisniewski et al, 2003), decreased spermatogenesis (Atanassova et al, 2000;West et al, 2005), lower FSH (Atanassova et al, 2000) and testosterone levels (Wisniewski et al, 2003), smaller ano-genital distance (Wisniewski et al, 2003(Wisniewski et al, , 2005 and alterations of reproductive and aggressive behavior (Wisniewski et al, 2003(Wisniewski et al, , 2005.…”
Section: Soy Phytoestrogens and Male Reproductive Functionmentioning
confidence: 99%
“…A further recent change in the Western diet is the increased use of soy-based infant formula milk (SFM) for the increasing numbers of babies that are lactose-intolerant [83]. Infants on SFM have a phytoestrogen (a kind of xenoestrogen) intake per kg bodyweight 6-11 times higher than that seen in adults consuming a high phytoestrogen diet [95].…”
Section: Xenoestrogensmentioning
confidence: 99%
“…It has also been described that these compounds cross a blood-tissue barrier similar to that of the testis, suggesting that intratubular germ cells might be exposed [82,83]. Genistein, the principal soy isoflavone, has estrogenic activity and is widely consumed.…”
Section: Xenoestrogensmentioning
confidence: 99%